Lithic studies Anatolia and beyond (Oxford)
vi, 278 sayfa
Keywords: “Lithic Studies : Anatolia and Beyond aims to show networks of cultural interactions by focusing on the latest lithic studies from Turkey, Greece, and the Balkans, bringing to the forefront the connectedness and techno-cultural continuity of knapped and ground stone technologies. Lithic studies are mostly conducted on a site by site basis, and specialist studies on lithics tend to focus primarily on technology and typology. As a result, information acquired through lithic research is presented as the identifier of the particular site with the addition of brief local correlations. This creates isolated islands of information. This volume is intended to bring these islands together to build the bigger picture, showcasing the fluidity of technological change, transitional cultural developments, and cultural formation by focusing on the interrelations between sites, localities and regions. Individually and collectively the wide range of papers in the volume give perspectives on Neolithization as seen through stone technologies, highlighting both regional trends and interregional relationships. The volume lays the foundations for creating an integrated understanding of Neolithic lithic technologies across the broad geographical regions of Turkey, Greece and the Balkans“ --